Self-regulated learning and creative thinking skills of elementary school students in the distance education during the COVID-19 pandemic - Maryani, Ika; Estriningrum, Ummu; Nuryana, Zalik (Creativity Studies, 2023)
The research aimed to know the relation between self-regulated learning and creative thinking skills of elementary school students in the distance education during COVID-19 pandemic. Self-regulated learning and creative thinking skills are needed by elementary school students. They train the students’ cognitive development during the learning process and prepare them for the next educational level. Teachers should guide, encourage, and implement appropriate learning strategies to improve the students’ self-regulated learning and creative thinking skills. It employed a quantitative approach with ex post facto and survey methods. The sample was 121 elementary school students taken randomly in Sleman Regency, Indonesia. The data were collected using a Likert scale questionnaire. The results showed that the students’ self-regulated learning level was in the moderate category, which was the highest frequency. The creative thinking skills also reached the same level and frequency. Further, self-regulated learning and creative thinking skills were correlated with a high correlation coefficient rate (R = 0.856). Therefore, it is recommended that teachers use a learning method that can activate and develop the self-regulated learning to increase the students’ creative thinking skills.